Overview Of Family Knowledge Level About Stroke Patient Care At prof. Dr. H. Aloei Saboe Hospital - Arsad, Sitti Fatimah Meylandri; Sitti Rahma; Abdul Rahman Ahmad (International Journal of Education, Vocational and Social Science, 2024)
Stroke is a condition or disease caused by a disorder in blood circulation in the brain, either because there is a blockage or bleeding due to rupture of blood vessels that result in paralysis or reduced strength in all or part of the body's muscles (hemiparesis). This condition can cause stroke sufferers to experience limitations in meeting their needs so that they need treatment and recovery assistance from the closest people such as family. Therefore, the family who plays a role in this must have knowledge about the care of family members who have had a stroke. This study aims to find out the overview of the level of family knowledge about the care of stroke patients at Prof. Dr. H. Aloei Saboe Hospital. This research is a quantitative research with a descriptive research design. The sampling technique used was accidental sampling with a sample of 92 respondents. The results of the study found that respondents had a good level of knowledge as many as 11 respondents (12%), a sufficient level of knowledge as many as 33 respondents (35.9%), and a lack level of knowledge as many as 48 respondents (52.1%). The conclusion of the study was that the majority of respondents had a low level of knowledge about the care of stroke patients.